1992
DOI: 10.1111/j.1600-0714.1992.tb00102.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in saliva of epileptic patients

Abstract: Unstimulated whole saliva samples of 27 indoor epileptic patients were studied on their protein composition using biochemical and immunochemical methods. A number of salivary proteins appeared at least partially to be hydrolyzed. In a number of saliva samples the concentration of carbohydrate-containing isoenzymes of amylase was reduced. In addition, the concentration of the 20 kD glycoprotein EP-GP was reduced by 60%. Sialic acid, the terminal sugar of the glycoproteins and mucins, was released for about 50% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

1995
1995
2008
2008

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…The deglycosylation reported for mucins of epileptic patients likewise reduced the ability of their saliva to aggregate oral streptococci. This change was seen for strains of S. sanguis but not S. oralis (Nieuw Amerongen et al, 1992). Another study has reported that those two species may collaborate in breaking down mucin oligosaccharides (Van der Hoeven and Camp, 1991).…”
Section: (C) Protein Polymorphismsmentioning
confidence: 82%
“…The deglycosylation reported for mucins of epileptic patients likewise reduced the ability of their saliva to aggregate oral streptococci. This change was seen for strains of S. sanguis but not S. oralis (Nieuw Amerongen et al, 1992). Another study has reported that those two species may collaborate in breaking down mucin oligosaccharides (Van der Hoeven and Camp, 1991).…”
Section: (C) Protein Polymorphismsmentioning
confidence: 82%
“…The amount of free sialic acid may be used as an indicator of bacterial neuraminidase activity, a measure of bacterial degradation in saliva [24]. Neuraminidase (sialidase) is an exo-glucosidase which hydrolyses a-glycosidically bound sialic acids found as terminal constituents of glycoproteins, glycolipids and oligosaccharides in higher animals and some microorganisms [25].…”
Section: Discussionmentioning
confidence: 99%
“…Quantitative alterations of these proteins in the saliva have been increasingly involved in the diagnosis of oral and systemic diseases (14,21,23,28). Among a number of analytical procedures for salivary proteins, electrophoresis has become an advantageous tool given its power to resolve relatively high number of macromolecules from a small sample.…”
mentioning
confidence: 99%